Room temperature Z-selective hydrogenation of alkynes by hemilabile and non-innocent (NNN)Co(ii) catalysts - Sharma, Dipesh M.; Gouda, Chandrakant; Gonnade, Rajesh G.; Punji, Benudhar (Catalysis Science & Technology, 2022)
Hemilabile and phosphine-free quinolinyl-based NNN-type pincer and non-pincer cobalt complexes were developed for the room temperature catalytic transfer semi-hydrogenation of alkynes to Z-alkenes. Treatment of the quinolinyl-amine ligand, [C9H6N(NH)CH2CH2NEt2] ((NNN2NEt2)-N-Q-N-CH)-H with CoX2 afforded the pincer complexes kappa(3)-((NNN2NEt2)-N-Q-N-CH)CoX2 (X = Cl, Br), whereas, the quinolinyl-amide ligand, [C9H6N(NH)C(O)CH2NEt2] ((NNNNEt2)-N-Q-N-C(O))-H gave chelate anionic complexes kappa(2)-((NN)-N-Q)CoX2((NHNEt2)-H-C(O)) (X = Cl, Br). The well-defined anionic non-pincer cobalt complexes efficiently catalyzed the semi-hydrogenation of diverse alkynes to deliver highly chemoselective and stereodivergent Z-alkenes at room temperature. This hydrogenation exhibited broad substrate scope with the tolerance of sensitive functional groups, such as -Cl, -Br, -I, -OH, -NH2, -COOMe, and pyridinyl, employing a stable and user-friendly ammonia borane hydrogen source.